Protestantism; Spirit of Capitalism and Inequality - Giri, Prakash Chandra (Journal of Interdisciplinary Studies, 2022)
Max Weber, a German Sociologist, clearly states that one of the key factors of capitalism is the Protestantism and its religious values. He critically argues that the religious ideas and concepts of groups like Protestants promoted the capitalistic spirit. He further explores that the religion is one of the key causes of the modern economic conditions. Even though there are some critiques and opponent views, he states protestant (Calvinism) helped to bring a dimension and a stage for the social development of capitalism. Therefore, it was a first major analysis of the effect of religion to form an economic system because Protestantism was one supporting factor for the Capitalistic spirit which also led inequality.